Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

Co-modified rice starch by extrusion and GML: multi-level structure - Jiaqi Song; Chong Cui; Zhuang Yang; Shiwen Cheng; Fan Yu; Jiangkai Zeng; Xiaoqi Ma; Xiaoshuai Yu; Zhigang Xiao; Lishuang Wang (Journal of Food Engineering, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Ag@BiPO4/MXene derived from F-containing nitrobenzene wastewater for efficient photocatalytic production of H2O2 - Die Zhou; Yu Liu; Guoqiang Shi; Diao Zhao; Xiyuan Cheng; Ren Cui; Daomei Chen; Jiaqiang Wang (Journal of Environmental Chemical Engineering, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Semi-Analytical Solution to 3D Tunneling Face Stability Considering Excess Pore Pressure - Yang Cheng; Zi-Xuan Cui; Ze-Hang Qian; Zhen-Yu Yin; Wan-Huan Zhou (Transportation Geotechnics, 2026)

Preparation and performance evaluation of a novel Tween 80-based microemulsion system for the remediation of petroleum hydrocarbon-contaminated soil using soil washing test - Peng Ye; Zhibin Liu; Chenfei He; Haitao Yu; Changsong Zhang; Xueke Zang; Hang Cui; Zhengbing Li; Liangliang Lu; Shiju Cheng (Environmental Research, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Opposite effects of garlic essential oil and protein fertilizer on aerial hyphae outbreak of wine-cap mushrooms: Mechanisms involving the redox imbalance and membrane destabilization - Xinran Yin; HongLin An; Xiaoya Zhao; Hui Cui; Lei Yu; Yanan Sun; Weina Li; Demei Meng; Yang Nie; Xia Gao; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

Synthesis of octenyl succinic anhydride-modified corn starch: Focusing on the C2, C3 and C6 substitution positions of anhydroglucose units - Wei Gao; Yifan Chen; Yue Cheng; Xuemin Kang; Xingtao Yu; Wenguo Wang; Bo Cui; A.M. Abd El-Aty (Food Chemistry, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Paeoniflorin's role in inhibiting malignant metastasis of gastrointestinal stromal tumors via CYP3A4 modulation - Dapeng Cui; Zeyin Cui; Yansen Li; Shuang Fan; Lei Li; Cheng Yang; Ruixia Yu; Jiaxin Cui; Runjia Fu; Jiandong Fei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Study on seepage characteristics of coal fracture networks based on fractal theory and micro-CT - Wenting Cui; Yanbin Yu; Weimin Cheng; Jie Zang; Zihao Yuan (Bulletin of Engineering Geology and the Environment, 2026)

n ‐Alkane Gradients Reshape Soil Microbial Networks and Functions at Petroleum Refinery Sites - Youru Zhang; Shixuan Cui; Yu Zhang; Jizhuang Chu; Kaiyue Liu; Xinjie Shan; Na Wang; Shudi Yao; Qiang Kong; Cheng Dong; Huanxin Zhang (Environmental Microbiology, 2026)
Petroleum refining activities exert substantial contamination pressure on soil ecosystems, yet the corresponding microbial response mechanisms remain insufficiently understood. This study integrates source apportionment, high‐throughput sequencing and co‐occurrence network analysis to elucidate microbial adaptations along a petroleum exposure gradient. Source analysis confirmed that all soils were predominantly influenced by petroleum‐derived inputs, with hydrocarbon concentrations increasing significantly across gradients. Under contamination levels of 422.35–621.21 mg/kg, petroleum pollution not only reduced soil total organic carbon (TOC) but also induced coupled C–N interactions and altered soil physicochemical properties, resulting in complex environmental effects. The soil quality index (SQI) exhibited a nonlinear trend, first decreasing and then increasing, with moderate overall levels (0.40–0.45). Functional diversity analyses indicated functional convergence rather than loss under contamination stress. At the metabolic level, low exposure primarily stimulated naphthalene degradation and detoxification pathways, whereas high exposure shifted microbial functions towards oxidative stress resistance and membrane structural remodelling. Meanwhile, microbial networks transitioned from densely connected but disturbance‐sensitive structures at low exposure to simplified yet more stable and robust configurations at high exposure. These findings provide mechanistic insights into microbial adaptation in petroleum‐contaminated soils and offer theoretical support for bioremediation strategies.

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

An efficient synthesis of halogenated 1,4,5,8-tetramethoxynaphthalenes - Gaoyang Yuan; Chenwu Liu; Jiqing Chen; Taohong Shi; Shouyan Xiang; Xiao Yu; Qilai Cheng; Jiahua Cui (Natural Product Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Microemulsion flushing of petroleum hydrocarbons in porous media: Microfluidic insights into residual oil morphologies and removal mechanisms - Peng Ye; Zhibin Liu; Chenfei He; Haitao Yu; Changsong Zhang; Xueke Zang; Hang Cui; Zhengbing Li; Liangliang Lu; Shiju Cheng; Quanbin Jin (Journal of Environmental Management, 2026)

Combining staged combustion and oxygen enrichment for stable and low-NOx porous media combustion of ammonia - Heng Zhang; Bang Cui; Jianguo Du; Zhou Yu; Xiong Liang; Yi-Bing Cheng; Yu Wang (Fuel, 2026)

Top-down constraint on CO emissions by incorporating emission heights: insights from COVID-19 activity changes in Nanchang city, China - Cheng Hu; Xuejing Shi; Lingjun Xia; Qitao Xiao; Guoqiang Bai; Fan Sun; Yifan Zhang; Yu Cui (Atmospheric Pollution Research, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Genomic selection accelerates genetic improvement of tolerance to visceral nodular disease in the half-smooth tongue sole (Cynoglossus semilaevis) - Mengyang Chang; Kunpeng Shi; Jibin Shen; Yu Yang; Yishuai Li; Jiayu Cheng; Xiangming Cheng; Yingming Yang; Zhongkai Cui; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Insight into the adsorption mechanism of gallium, vanadium on amidoxime resin and cascade desorption for synergistic recovery - Li Cui; Muyang Chen; Yu Zhang; Lijuan Wang; Bo Yang; Fangqin Cheng (Chemical Engineering Journal, 2026)

Room-Temperature Fabrication of Dual-Functional SiO2/TiO2 Coating for Photovoltaic Efficiency Enhancement: From Laboratory Development to Field Validation - Pengge Wang; Xinwei Li; Ning Zhang; Yue Zhai; Zhenyu Wang; Long Cui; Suixin Liu; Wingkei Ho; Yu Huang; Shun-cheng Lee (Aerosol Science and Engineering, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Constructing a PANoptosis-based prognostic signature to evaluate the immune landscape and therapeutic response in clear cell renal cell carcinoma - Yu Dong; Zitong Yang; Zhinan Xia; Jiahao Liao; Zhiming Cui; Shenhao Xu; Bing Liu; Liangliang Ren; Tengda Wang; Wei Guo; Shuwen Wang; Yuyong Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Population Genomics and Climate Change Vulnerability in Two Sympatric Desert Rodents - Tian Tian; Jilong Cheng; Yu Zhang; Lin Xia; Yilin Chen; Fangyuan Yang; Zhixin Wen; Yaqian Cui; Weibo Wang; Xueying Zhang; Yanhua Qu; Qisen Yang (Global Change Biology, 2025)
Climate change poses a severe threat to desert ecosystems; however, understanding how specialized desert species respond to changing climate remains limited. These species are confronting extreme changes, including intensified droughts, altered precipitation, and temperature patterns. Here, we integrate population and ecogenomic approaches to examine population genetic structure, demographic history, and climate adaptation in two distantly related, sympatric rodent species in arid and semi‐arid regions in East Asia. We further combine genomic offset analysis, ecological niche modeling, and landscape connectivity assessments to evaluate their climate change risks. Our results reveal that the two species have diverged into five geographically distinct lineages, each associated with a different arid region. Lineage divergence times are estimated between 20 and 400 thousand years ago, with population size declines occurring around the Last Glacial Maximum. While the two species exhibited distinct climate adaptation, evidenced by different key climatic variables and associated genes identified for each species, they exhibited congruent vulnerability to future climate change. This was indicated by parallel patterns of genomic offset and niche suitability loss. Under future climate change scenarios, eastern lineages in high precipitation seasonality areas (e.g., DB lineages in Horqin Sandy Land) face a higher risk due to substantial genomic offset, habitat loss, and reduced connectivity. In contrast, lineages on the west ranges with low precipitation seasonality (e.g., QH lineages in the Qaidam Basin and HL lineage in the Changtang Plateau) appear less vulnerable, characterized by lower genomic offset and the expansion of desert habitats. Overall, this study provides a comprehensive framework for identifying vulnerable populations and predicting responses to climate changes in desert species, offering critical insights for the conservation of desert ecosystems.

Slightly acidic electrolyzed water induces Staphylococcus aureus to enter the VBNC state: differences between planktonic and biofilm states bacteria - Ziyi Zhang; Jingqi Feng; Haoran Cui; Yu Wu; Yihong Wang; Weipeng Xu; Yiming Lu; Menghua Duan; Hui Yang; Shuai Cheng; Xiaolin Cai; Chunling Zhang; et al. (Food Research International, 2025)

Experimental study of localized hydro-thermal-mechanical coupling characteristics of unsaturated silt under step-freezing conditions - Yu-zhi Zhang; Cheng-yan Li; Meng Wang; Yi-han Cui; You-cheng Sun (Cold Regions Science and Technology, 2025)

Pinocembrin Alleviates Postoperative Cognitive Dysfunction in Aged Mice by Modulating miR-384-5p/FZD1 Axis to Activate the Wnt/β-Catenin Pathway - Jie Li; Xue-li Peng; Xin-yu Cheng; Jun-jun Yang; Cui Cui; Jian-hui Liu (Molecular Neurobiology, 2025)

A customized immunomodulator reinforces the T cell-mediated immunological cascade for cancer therapy - Guowang Cheng; Jiaxin Wu; Wei Liu; Yumiao Yang; Hao Cui; Xiuxiu Dai; Bowen Li; Zhen Tian; Xiaojia Chen; Xiaohui Li; Zhenfeng Wu; Guochao Liao; et al. (Chemical Engineering Journal, 2025)

Inhibition by dissolved organic matter of the degradation of purine compounds by the sulfate radical - Shuangshuang Cheng; Rui Cui; Jinpeng Yu; Yujie Zhao; Xin Yang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Cooperative nuclear import of duck plague virus DNA polymerase subunits: pUL42 NLS Enhances pUL30 nuclear import and viral replication, with VP22 as a compensatory factor - Yuxi Cui; Mingshu Wang; Anchun Cheng; Qiao Yang; Xumin Ou; Di Sun; Yu He; Xinxin Zhao; Ying Wu; Shaqiu Zhang; Bin Tian; Juan Huang; et al. (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

Biomimetic photosynthesis nanoreactors based thylakoid synergy with metformin for reversing tumor immunosuppressive microenvironment therapy - Peiliang Zhong; Yuyue Zhao; Hao Cui; Guowang Cheng; Linze Xia; Zhen Tian; Wei Liu; Jiaxin Wu; Jiaxian Yu; Xinyi Peng; Guangtao Yu; Dandan Ma (Chemical Engineering Journal, 2025)

Pilot Exploration of RGMa-BMP4 Signaling in Neutrophil Activation in NMOSD: Integrating Clinical and Molecular Insights - Weihe Zhang; Lei Cui; Yeqiong Zhang; Yang He; Xiaoxuan Li; Yu Wang; Jinsong Jiao; Dantao Peng; Ming Jin; Cheng Xiao (Molecular Neurobiology, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Imaging brain white matter function using resting-state functional MRI - Gong-Jun Ji; Zaixu Cui; Ryan C.N. D’Arcy; Wei Liao; Bharat B. Biswal; Qing Zhang; Cheng Luo; Yu-Feng Zang; Zhaohua Ding; Xi-Nian Zuo; John C. Gore; Kai Wang (Science Bulletin, 2025)

Unveiling the mechanism of Gelatin's influence on starch digestibility: A focus on amylopectin chain distribution - Yifan Chen; Yue Cheng; Wei Gao; Xuemin Kang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Hydrocolloids, 2025)

Observed CO2 concentration reveals steep decrease of anthropogenic emissions in winters of 2021 and 2022 in Hangzhou and Yangtze River Delta region, China - Cheng Hu; Huili Liu; Yifan Zhang; Yu Cui; Fan Sun; Xuejing Shi; Junqing Zhang; Yanrong Yang; Leying Zhang; Bing Qi; Qitao Xiao; Ning Hu; et al. (Science of The Total Environment, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

A new method for quantitative characterization of dynamic migration behavior of NaCl in beef during marinating - Yingjie Feng; Fujia Dong; Cheng Wu; Jiarui Cui; Guangxian Wang; Zhongxiong Zhang; Songmin Cao; Sijia Liu; Hui Li; Yingkun Shi; Jianguo Yu; Songlei Wang (Food Research International, 2025)

Benzene-induced hematotoxicity enhances the self-renewal ability of HSPCs in Mll-Af9 mice - Jin Zhou; Pinpin Sui; Jianxin Zhao; Xiurong Cheng; Tao Yu; Shiwei Cui; Xiangrong Song; Caihong Xing (Toxicology, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Probabilistic mapping of imbalanced data for groundwater contamination using classification algorithms: Performance and reliability - Yang Qiu; Aiguo Zhou; Hanxiang Xiong; Defang Zhang; Cheng Su; Shizheng Zhou; Lin Go; Chi Yang; Hao Cui; Wei Fan; Yao Yu; Fawang Zhang; et al. (Groundwater for Sustainable Development, 2025)

Detection and molecular epidemiology of canine parvovirus and identification of highly pathogenic CPV-2c isolates from Shandong, China - Jiahui Li; Baoyu Cheng; Zihe Li; Yanlei Cui; Haiyan Yang; Weiquan Liu; Chuanmei Zhang; Yongle Yu (Virus Genes, 2025)

The reverse-reduction effect of dissolved organic matter on the degradation of micropollutants induced by halogen radicals (Cl2•- and Br2•-) - Shuangshuang Cheng; Rui Cui; Yangjian Zhou; Yu Lei; Ni Wang; Yanheng Pan; Xin Yang (Water Research, 2025)

Simulation study on the effect of temperature on hydrogen production performance of alkaline electrolytic water - Xiaobing Bi; Gan Wang; Daan Cui; Xinyi Qu; Shuaishuai Shi; Dong Yu; Mojie Cheng; Yulong Ji (Fuel, 2025)

Lymphatic absorption characteristics of eicosapentaenoic acid -enriched phosphoethanolamine plasmalogen and its gastric and intestinal hydrolysates - Dan-Dan Wang; Xiao-Yu Cui; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Teruyoshi Yanagita; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2025)

Generation of unpaired electrons to promote electron transfer at the cathode of room-temperature sodium sulfur batteries - Chen Huang; Jing Yu; Yao-Jie Lei; Oleg Usoltsev; Li Gong; Zhibiao Cui; Junshan Li; Canhuang Li; Bingfei Nan; Xuan Lu; Ren He; Xuede Qi; et al. (Chemical Engineering Journal, 2025)

Determining the geographical origins of goji berries using the Twin-Tower model for Multi-Feature - Jiarui Cui; Cheng Wu; Shibo Pan; Kenken Li; Sijia Liu; Yu Lv; Songlei Wang; Ruiming Luo (Computers and Electronics in Agriculture, 2024)

Fabrication of fluorinated magnetic microporous organic network for selective and efficient extraction of benzoylurea insecticides in tea beverages - Hui-Ping Yu; Qian-Qian Xu; Xin Wang; Yuan-Yuan Cui; He-Fang Wang; Cheng-Xiong Yang (Food Chemistry, 2024)

Engineering of calcium overload for state-of-the-art tumor therapy - Xinping Liu; Hui Hu; Jinjin Chen; Yi Li; Yaming Cheng; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

Engineering microalgae for robust glycolate biosynthesis: Targeted knockout of hydroxypyruvate reductase 1 combined with optimized culture conditions enhance glycolate production in Chlamydomonas reinhardtii - Suihao Yan; Yuyong Hou; Meijie Cui; Tingfeng Cheng; Sihan Lu; Zhiyong Liu; Bicheng Deng; Weijia Liu; Menglin Shi; Liangcai Lin; Longjiang Yu; Lei Zhao (Bioresource Technology, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Safety performance evaluation of offshore high integrity pressure protection system using multiphase dynamic Bayesian network methodology - Yang Yu; Yuqing Liang; Shibo Wu; Baoping Cai; Yu Pan; Ruilong Gao; Siyuan Cheng; Yupeng Cui; Yuheng Yang; Hao Guo (Ocean Engineering, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Synergistic effects of biochar and laccase on nitrogen conversation and degradations of two artificial sweeteners during the sewage sludge composting - Jishao Jiang; Huilin Cui; Zhuyu Tang; Shipeng Wang; Ke Cheng; Chunyan Zhang; Tonghuan Yu; Jinghua Lv; Fuqiang Yu; Dong Liu (Chemical Engineering Journal, 2024)

Progressive failure characteristics of coal under uniaxial compression: A comprehensive application of micro-ct and digital volume correlation - Yanbin Yu; Chuanwen Ni; Wenting Cui; Weimin Cheng; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Lnc-HIBADH-4 Regulates Autophagy-Lysosome Pathway in Amyotrophic Lateral Sclerosis by Targeting Cathepsin D - Jingxuan Huang; Yujiao Yu; Dejiang Pang; Chunyu Li; Qianqian Wei; Yangfan Cheng; Yiyuan Cui; Ruwei Ou; Huifang Shang (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is the most prevalent and lethal class of severe motor neuron diseases (MND) with no efficacious treatment. The pathogenic mechanisms underlying ALS remain unclear. Nearly 90% of patients exhibit sporadic onset (sALS). Therefore, elucidating the pathophysiology of ALS is imperative. Long non-coding RNA (lncRNA) is a large class of non-coding RNAs that regulate transcription, translation, and post-translational processes. LncRNAs contribute to the pathogenesis of diverse neurodegenerative disorders and hold promise as targets for interference in the realm of neurodegeneration. However, the mechanisms of which lncRNAs are involved in ALS have not been thoroughly investigated. We identified and validated a downregulated lncRNA, lnc-HIBADH-4, in ALS which correlated with disease severity and overall survival. Lnc-HIBADH-4 acted as a “molecular sponge” regulating lysosomal function through the lnc-HIBADH-4/miR-326/CTSD pathway, thereby impacting autophagy-lysosome dynamics and the levels of cell proliferation and apoptosis. Therefore, this study discovered and revealed the role of lnc-HIBADH-4 in the pathogenesis of ALS. With further research, lnc-HIBADH-4 is expected to provide a new biomarker in the diagnosis and treatment of ALS.

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Efficient detection of geosmin and 2-methylisoborneol in natural/drinking water by UIO66-NH2 composite-derived porous carbon - Wei Liu; Ming Yang; Shuang Wang; Yan-Sai Bao; Yong-He Cui; Ling-Xu Meng; Liang-Cheng Li; Yang Wu; Yu-Yang Zhang (Journal of Environmental Chemical Engineering, 2024)

Bright cyan emission from Eu-Doped borosilicate glasses by optimizing reduction of Eu3+ to Eu2+ in ambient atmosphere - Jiuzhi Cui; Yufeng Wen; Runchuan Chen; Xi Cheng; Meidong Yu; Jiandi Liu; Zuofu Hu; Jiajun He; Zhuohao Xiao; Xin-Yuan Sun (Chemical Engineering Journal, 2024)

Di-n-butyl phthalate induces toxicity in male fetal mouse testicular development by regulating the MAPK signaling pathway - Xinwei Wan; Xudong Cui; Xiang Wang; Mingyang Feng; Shinan Wei; Jia Yu; Sha Cheng; Heng Luo; Jianxin Hu (Toxicology and Applied Pharmacology, 2024)

Multi-performance reliability-based concept-detailed co-design of offshore structures using modified conjugate FR algorithm - Yupeng Cui; Yang Yu; Siyuan Cheng; Mingxiu Wei; Yu Pan; Zewei Dong (Ocean Engineering, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Evolution rules of coal mesopore structure under the action of hydraulic coupling - Yanbin Yu; Ruoyu Mu; Weimin Cheng; Wenting Cui; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

A novel BACG inverse reliability algorithm for efficient and robust reliability-based topology optimization of marine structures - Yupeng Cui; Baolei Zhang; Yang Yu; Siyuan Cheng; Mingxiu Wei; Zihang Jin; Lin Song (Ocean Engineering, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Microstructure evolution law and dissolution time effect of bituminous coal under acetic acid acidification: Based on Micro-CT image analysis - Yanbin Yu; Hao Xing; Weimin Cheng; Wenting Cui; Yongtao Chen (Fuel, 2024)

Effects of starch–fatty acid complexes with different fatty acid chain lengths and degrees of saturation on the rheological and 3D printing properties of corn starch - Yue Cheng; Wei Gao; Xuemin Kang; Jianfei Wang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Chemistry, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

A novel tool for tracing water sources of streamflow in a mixed land-use catchment - Zhi-Xiang Sun; Jun-Fang Cui; Jian-Hua Cheng; Xiang-Yu Tang (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

MEIC-global-CO2: A new global CO2 emission inventory with highly-resolved source category and sub-country information - Ruochong Xu; Dan Tong; Qingyang Xiao; Xinying Qin; Cuihong Chen; Liu Yan; Jing Cheng; Can Cui; Hanwen Hu; Wenyu Liu; Xizhe Yan; Huaxuan Wang; et al. (Science China Earth Sciences, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Effect of sesbania gum on the rheological, textural, and microstructural characteristics of CaSO4-induced soy protein isolate gels - Ran Yang; Bin Yu; Laixue Ni; Yungang Cao; Qingqing Chai; Haiteng Tao; Zheng Zhang; Guimei Liu; Yunhui Cheng; Haibo Zhao; Bo Cui; Zhengzong Wu (Food Hydrocolloids, 2024)

Estimating leaf age of maize seedlings using UAV-based RGB and multispectral images - Yi Bai; Liangsheng Shi; Yuanyuan Zha; Shuaibing Liu; Chenwei Nie; Honggen Xu; Hongye Yang; Mingchao Shao; Xun Yu; Minghan Cheng; Yadong Liu; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Research on motion control of the semi-submersible platform under the mooring line failure - Siyuan Cheng; Yang Yu; Penghui Zhang; Baolei Zhang; Yupeng Cui; Zhengxin Huang; Xiaoming Zhang; Jianxin Yu; Zhenglong Yang (Ocean Engineering, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

A review of remote sensing estimation of crop water productivity: definition, methodology, scale, and evaluation - Minghan Cheng; Dameng Yin; Wenbin Wu; Ningbo Cui; Chenwei Nie; Lei Shi; Shuaibing Liu; Xun Yu; Yi Bai; Yadong Liu; Yuqin Zhu; Xiuliang Jin (International Journal of Remote Sensing, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Quantifying effect of maize tassels on LAI estimation based on multispectral imagery and machine learning methods - Mingchao Shao; Chenwei Nie; Aijun Zhang; Liangsheng Shi; Yuanyuan Zha; Honggen Xu; Hongye Yang; Xun Yu; Yi Bai; Shuaibing Liu; Minghan Cheng; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Mooring line failure diagnosis and motion control of semi-submersible platform based on the predictive model - Yang Yu; Siyuan Cheng; Yupeng Cui; Xiaoming Zhang; Penghui Zhang; Jianxing Yu (Ocean Engineering, 2023)

Novel bimetallic chalcogenide adsorbents for elemental mercury removal from flue gas: A review - Xin Yang; Chen Gong; Yu Guan; Jingyi Li; Fangqin Li; Cheng Peng; Jiang Wu; Tianhui Cui; Shang Xiang; Yuan Gao (Fuel, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Using transcriptomics to reveal the molecular mechanism of higher alcohol metabolism in Saccharomyces cerevisiae - Danyao Cui; Ling Liu; Xiaoyuan Zhang; Liangcai Lin; Xin Li; Ting Cheng; Chunhui Wei; Yu Zhang; Zheng Zhou; Wei Li; Cuiying Zhang (Food Bioscience, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Amygdalin alleviated TGF-β-induced epithelial-mesenchymal transition in bronchial epithelial cells - An-nan Zhang; Nan Li; Zhuo-chang Chen; Ya-li Guo; Cui-jie Tian; Dong-jun Cheng; Xue-yi Tang; Xiao-yu Zhang (Chemico-Biological Interactions, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Waveform Design Using Coprime Frequency-Modulated Pulse Trains for Reverberation Suppression of Active Sonar - Xiaobin Cui; Cheng Chi; Shuqiu Li; Zigao Li; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
Over the last two decades, low-frequency active sonar has become an attractive tool for underwater target detection. The reverberation to signal ratio (RSR) of transmitted waveforms is an important factor affecting the detection capability of low-frequency active sonar. Therefore, reasonable waveform design for reverberation suppression of active sonar is an important topic. Pulse trains of linear frequency-modulated (PTFM) waveforms have been proposed and manifested their good performance in suppressing reverberation. The number of sub-pulses is positively related to the reverberation to signal ratio; the lower the number of sub-pulses, the lower the reverberation to signal ratio. However, to avoid ambiguity in a Doppler measurement, the PTFM waveforms have a requirement for the number of sub-pulses to be satisfied, which prevents its reverberation suppression performance from being further improved. In this paper, we propose a coprime pulse train of linear frequency-modulated (CPTFM) waveform, which reduces the number of sub-pulses to some extent. Therefore, the ability of reverberation suppression of the CPTFM waveform can be improved. The RSR was chosen as the metric to evaluate the waveform’s ability to suppress reverberation, and the theoretical formula for the RSR of the CPTFM waveform was derived in zone A and B. With the overlap of zones A and B brought about by the decrease in the number of sub-pulses, the average RSR of zones A and B is used in this paper to evaluate the reverberation suppression ability of the waveform. The simulation experiment shows that the proposed CPTFM waveform decreases the average RSR by 7 dB and 20 dB in comparison to the reference PTFM waveform and continuous waveform (CW), which is consistent with the theoretical results by the derived formulas.

Anti-Seizure and Neuronal Protective Effects of Irisin in Kainic Acid-Induced Chronic Epilepsy Model with Spontaneous Seizures - Jie Yu; Yao Cheng; Yaru Cui; Yujie Zhai; Wenshen Zhang; Mengdi Zhang; Wenyu Xin; Jia Liang; Xiaohong Pan; Qiaoyun Wang; Hongliu Sun (Neuroscience Bulletin, 2022)

Hydrogen Sulfide Attenuates High-Fat Diet-Induced Obesity: Involvement of mTOR/IKK/NF-κB Signaling Pathway - Maofang Zhao; Yuan Cheng; Xiaoxuan Wang; Xiaoying Cui; Xiaojing Cheng; Qian Fu; Yilin Song; Peiquan Yu; Yi Liu; Yinghua Yu (Molecular Neurobiology, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Impacts of pavement on the growth and biomass of young pine, ash and maple trees - Bowen Cui; Xuming Wang; Yuebo Su; Yuanyuan Chen; Weiwei Yu; Cheng Gong; Li Li; Abdur Rehim; Xiaoke Wang (Trees, 2021)

Endocrine pheromones couple fat rationing to dauer diapause through HNF4α nuclear receptors - Cheng Gao; Qi Li; Jialei Yu; Shiwei Li; Qingpo Cui; Xiao Hu; Lifeng Chen; Shaobing O. Zhang (Science China Life Sciences, 2021)

A novel regQTL-SNP and the risk of lung cancer: a multi-dimensional study - Yuhui Yu; Liping Mao; Zhounan Cheng; Xiaoqi Zhu; Jiahua Cui; Xiaoyu Fu; Jingwen Cheng; Yan Zhou; Anni Qiu; Yang Dong; Xun Zhuang; Yihua Lu; et al. (Archives of Toxicology, 2021)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

SETD3 Downregulation Mediates PTEN Upregulation-Induced Ischemic Neuronal Death Through Suppression of Actin Polymerization and Mitochondrial Function - Xiangyu Xu; Yu Cui; Congqin Li; Yuyang Wang; Jing Cheng; Songfeng Chen; Jiangdong Sun; Jinyang Ren; Xujin Yao; Jingchen Gao; Xiaohong Huang; Qi Wan; et al. (Molecular Neurobiology, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Complex analysis of the personalized pharmacotherapy in the management of COVID-19 patients and suggestions for applications of predictive, preventive, and personalized medicine attitude - Lei-Yun Wang; Jia-Jia Cui; Qian-Ying OuYang; Yan Zhan; Yi-Min Wang; Xiang-Yang Xu; Lu-Lu Yu; Hui Yin; Yang Wang; Chen-Hui Luo; Cheng-Xian Guo; Ji-Ye Yin (EPMA Journal, 2021)
Aims Coronavirus disease 2019 (COVID-19) is rapidly spreading worldwide. Drug therapy is one of the major treatments, but contradictory results of clinical trials have been reported among different individuals. Furthermore, comprehensive analysis of personalized pharmacotherapy is still lacking. In this study, analyses were performed on 47 well-characterized COVID-19 drugs used in the personalized treatment of COVID-19. Methods Clinical trials with published results of drugs use for COVID-19 treatment were collected to evaluate drug efficacy. Drug-to-Drug Interactions (DDIs) were summarized and classified. Functional variations in actionable pharmacogenes were collected and systematically analysed. “Gene Score” and “Drug Score” were defined and calculated to systematically analyse ethnicity-based genetic differences, which are important for the safer use of COVID-19 drugs. Results Our results indicated that four antiviral agents (ritonavir, darunavir, daclatasvir and sofosbuvir) and three immune regulators (budesonide, colchicine and prednisone) as well as heparin and enalapril could generate the highest number of DDIs with common concomitantly utilized drugs. Eight drugs (ritonavir, daclatasvir, sofosbuvir, ribavirin, interferon alpha-2b, chloroquine, hydroxychloroquine (HCQ) and ceftriaxone had actionable pharmacogenomics (PGx) biomarkers among all ethnic groups. Fourteen drugs (ritonavir, daclatasvir, prednisone, dexamethasone, ribavirin, HCQ, ceftriaxone, zinc, interferon beta-1a, remdesivir, levofloxacin, lopinavir, human immunoglobulin G and losartan) showed significantly different pharmacogenomic characteristics in relation to the ethnic origin of the patient. Conclusion We recommend that particularly for patients with comorbidities to avoid serious DDIs, the predictive, preventive, and personalized medicine (PPPM, 3 PM) strategies have to be applied for COVID-19 treatment, and genetic tests should be performed for drugs with actionable pharmacogenes, especially in some ethnic groups with a higher frequency of functional variations, as our analysis showed. We also suggest that drugs associated with higher ethnic genetic differences should be given priority in future pharmacogenetic studies for COVID-19 management. To facilitate translation of our results into clinical practice, an approach conform with PPPM/3 PM principles was suggested. In summary, the proposed PPPM/3 PM attitude should be obligatory considered for the overall COVID-19 management.

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

The molecular mechanism of a novel derivative of BTO-956 induced apoptosis in human myelomonocytic lymphoma cells - Yu-Lin Li; De-Jun Zhou; Zheng-Guo Cui; Lu Sun; Qian-Wen Feng; Shahbaz Ahmad Zakki; Yusuke Hiraku; Cheng-Ai Wu; Hidekuni Inadera (Apoptosis, 2021)

miR-9-5p facilitates hepatocellular carcinoma cell proliferation, migration and invasion by targeting ESR1 - Libing Wang; Mingxin Cui; Daming Cheng; Fengzhi Qu; Jingkun Yu; Yanbin Wei; Ling Cheng; Xiaotang Wu; Xiaogang Liu (Molecular and Cellular Biochemistry, 2021)

Correction to: Long non-coding RNA H19 promotes osteogenic differentiation of renal interstitial fibroblasts through Wnt-β-catenin pathway - Zewu Zhu; Yu Cui; Fang Huang; Huimin Zeng; Weiping Xia; Feng Zeng; Cheng He; Jinbo Chen; Zhiyong Chen; Hequn Chen; Yang Li (Molecular and Cellular Biochemistry, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Long non-coding RNA H19 promotes osteogenic differentiation of renal interstitial fibroblasts through Wnt-β-catenin pathway - Zewu Zhu; Yu Cui; Fang Huang; Huimin Zeng; Weiping Xia; Feng Zeng; Cheng He; Jinbo Chen; Zhiyong Chen; Hequn Chen; Yang Li (Molecular and Cellular Biochemistry, 2020)

Expressional and Functional Verification of the Involvement of CmEXPA4 in Chrysanthemum Root Development - Hong Ren; Li-zhu Wen; Yun-hui Guo; Yuan-yuan Yu; Cui-hui Sun; Hong-mei Fan; Fang-fang Ma; Cheng-shu Zheng (Journal of Plant Growth Regulation, 2019)

Two new polyketides isolated from a diethyl sulphate mutant of marine-derived Penicillium purpurogenum G59 - Chang-Jing Wu; Hua Qiao; Cheng-Bin Cui; Yu Yang; Rui Xu; Chun-Xiao Sun; De-Hai Li; Chang-Wei Li (Natural Product Research, 2019)

2,3,7,8-Tetrachlorodibenzo-p-dioxin-induced aryl hydrocarbon receptor activation enhanced the suppressive function of mesenchymal stem cells against splenocyte proliferation - Guorui Zhang; Xiaoming Li; Yi Cheng; Haiyang Yu; Wen Gu; Zhilei Cui; Xuejun Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

CNOT3 contributes to cisplatin resistance in lung cancer through inhibiting RIPK3 expression - Lin Jing; Meng-En Zhai; Jian Cui; Xin-Yu Fan; Yuan-Yuan Cheng; Jian-Li Jiang; Zhi-Nan Chen (Apoptosis, 2019)

The cost of rapid and haphazard urbanization: lessons learned from the Freetown landslide disaster - Yifei Cui; Deqiang Cheng; Clarence E. Choi; Wen Jin; Yu Lei; Jeffrey S. Kargel (Landslides, 2019)

Effect and threshold of PM2.5 on population mortality in a highly polluted area: a study on applicability of standards - Runze Ye; Liangliang Cui; Xiumiao Peng; Kunkun Yu; Fang Cheng; Yakun Zhu; Chongqi Jia (Environmental Science and Pollution Research, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

Ascidiaceibacter salegens gen. nov., sp. nov., isolated from an ascidian - Lei Chen; Shi-Cheng Wang; Cui-Hong Ma; Dong-Xu Zheng; Zong-Jun Du; Guang-Yu Wang (Antonie van Leeuwenhoek, 2018)

Experimental infection of Marmota monax with a novel hepatitis A virus - Jie-mei Yu; Li-li Li; Guang-cheng Xie; Cui-yuan Zhang; Yuan-yun Ao; Zhao-jun Duan (Archives of Virology, 2018)

Temporal–spatial variability of atmospheric and hydrological natural disasters during recent 500 years in Inner Mongolia, China - Yu Peng; Jingyi Song; Tiantian Cui; Xiang Cheng (Natural Hazards, 2017)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

A preliminary study on ore-forming environments of Xianglushan-type iron deposit and the weathering mineralization of Emeishan basalt in Guizhou Province, China - Guofan Cheng; Youping Liu; Hansheng Long; Tao Cui; Ning Yu (Acta Geochimica, 2017)

Comparative Studies on the Toxicokinetics of Benzo[a]pyrene in Pinctada martensii and Perna viridis - Haihua Wang; Lili Cui; Huamin Cheng; Yu Zhang; Xiaoping Diao; Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

A Novel, Multi-Target Natural Drug Candidate, Matrine, Improves Cognitive Deficits in Alzheimer’s Disease Transgenic Mice by Inhibiting Aβ Aggregation and Blocking the RAGE/Aβ Axis - Lili Cui; Yujie Cai; Wanwen Cheng; Gen Liu; Jianghao Zhao; Hao Cao; Hua Tao; Yan Wang; Mingkang Yin; Tingting Liu; Yu Liu; Pengru Huang; et al. (Molecular Neurobiology, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Polypore diversity in North America with an annotated checklist - Li-Wei Zhou; Karen K. Nakasone; Harold H. Burdsall; James Ginns; Josef Vlasák; Otto Miettinen; Viacheslav Spirin; Tuomo Niemelä; Hai-Sheng Yuan; Shuang-Hui He; Bao-Kai Cui; Jia-Hui Xing; et al. (Mycological Progress, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Occurrence and Partitioning of Antibiotics in the Water Column and Bottom Sediments from the Intertidal Zone in the Bohai Bay, China - Dengmiao Cheng; Yujia Xie; Yanjun Yu; Xinhui Liu; Shengnan Zhao; Baoshan Cui; Junhong Bai (Wetlands, 2016)

Distribution and sources of the polycyclic aromatic hydrocarbons in the sediments of the Pearl River estuary, China - Jian-Dong Zhang; You-Shao Wang; Hao Cheng; Zhao-Yu Jiang; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Variation of phytoplankton community structure from the Pearl River estuary to South China Sea - Zhao-Yu Jiang; You-Shao Wang; Hao Cheng; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

Dynamics of the worldwide number of fungi with emphasis on fungal diversity in China - Yu-Cheng Dai; Bao-Kai Cui; Jing Si; Shuang-Hui He; Kevin D. Hyde; Hai-Sheng Yuan; Xiao-Yong Liu; Li-Wei Zhou (Mycological Progress, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2015)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Protoplast fusion enhances lignocellulolytic enzyme activities in Trichoderma reesei - Yu-xiao Cui; Jia-jing Liu; Yan Liu; Qi-yue Cheng; Qun Yu; Xin Chen; Xiao-dong Ren (Biotechnology Letters, 2014)

Erratum to: Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

Molecular cloning and characterization of NPR1 gene from Arachis hypogaea - Qi Wu; Xiu Zhen Wang; Yue Yi Tang; Hong Tao Yu; Yu Fei Ding; Chuan De Yang; Feng Gao Cui; Jian Cheng Zhang; Chuan Tang Wang (Molecular Biology Reports, 2014)

Flammeopellis bambusicola gen. et. sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and phylogenetic analysis - Chang-Lin Zhao; Xin-Sheng He; Kun-Yuan Wanghe; Bao-Kai Cui; Yu-Cheng Dai (Mycological Progress, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Activated macrophage-like synoviocytes are resistant to endoplasmic reticulum stress-induced apoptosis in antigen-induced arthritis - Li-Jie Feng; Tong-Cui Jiang; Cheng-Yue Zhou; Chang-Liang Yu; Yu-Jun Shen; Jun Li; Yu-Xian Shen (Inflammation Research, 2014)

Low Glucose Utilization and Neurodegenerative Changes Caused by Sodium Fluoride Exposure in Rat’s Developmental Brain - Chunyang Jiang; Shun Zhang; Hongliang Liu; Zhizhong Guan; Qiang Zeng; Cheng Zhang; Rongrong Lei; Tao Xia; Zhenglun Wang; Lu Yang; Yihu Chen; Xue Wu; et al. (NeuroMolecular Medicine, 2014)

Effect of BRAF V600E mutation on tumor response of anti-EGFR monoclonal antibodies for first-line metastatic colorectal cancer treatment: a meta-analysis of randomized studies - Dandan Cui; Dan Cao; Yu Yang; Meng Qiu; Ying Huang; Cheng Yi (Molecular Biology Reports, 2014)

Taxonomy and phylogeny of Ceriporia (Polyporales, Basidiomycota) with an emphasis of Chinese collections - Bi-Si Jia; Li-Wei Zhou; Bao-Kai Cui; Bernard Rivoire; Yu-Cheng Dai (Mycological Progress, 2014)

Molecular phylogeny and morphology reveal a new species of Amyloporia (Basidiomycota) from China - Bao-Kai Cui; Yu-Cheng Dai (Antonie van Leeuwenhoek, 2013)

Rapid development of 36 polymorphic microsatellite markers for Tetranychus truncatus by transferring from Tetranychus urticae - Cheng Ge; Jing-Tao Sun; Yu-Nan Cui; Xiao-Yue Hong (Experimental and Applied Acarology, 2013)

An experimental and numerical study of the freak wave speed - Cheng Cui; Ningchuan Zhang; Haigui Kang; Yuxiu Yu (Acta Oceanologica Sinica, 2013)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Effects of pyrene on antioxidant systems and lipid peroxidation level in mangrove plants, Bruguiera gymnorrhiza - Hui Song; You-Shao Wang; Cui-Ci Sun; Yu-Tu Wang; Ya-Lan Peng; Hao Cheng (Ecotoxicology, 2012)

The Influence of Fluoride on the Expression of Inhibitors of Wnt/β-Catenin Signaling Pathway in Rat Skin Fibroblast Cells - Xiao-Li Liu; Chang-Cheng Li; Ke-Jian Liu; Cai-Yan Cui; Yu-Zeng Zhang; Yun Liu (Biological Trace Element Research, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Identification of single nucleotide polymorphisms and haplotypes associated with yield and yield components in soybean (Glycine max) landraces across multiple environments - Derong Hao; Hao Cheng; Zhitong Yin; Shiyou Cui; Dan Zhang; Hui Wang; Deyue Yu (Theoretical and Applied Genetics, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Three new species of Inonotus (Basidiomycota, Hymenochaetaceae) from China - Bao-Kai Cui; Ping Du; Yu-Cheng Dai (Mycological Progress, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Finger-vein image recognition combining modified Hausdorff distance with minutiae feature matching - Cheng-Bo Yu; Hua-Feng Qin; Yan-Zhe Cui; Xiao-Qian Hu (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Trichaptum (Basidiomycota, Hymenochaetales) from China with a description of three new species - Yu-Cheng Dai; Bao-Kai Cui; Hai-Sheng Yuan (Mycological Progress, 2009)

Detection of quantitative trait loci for phosphorus deficiency tolerance at soybean seedling stage - Dan Zhang; Hao Cheng; Leiyue Geng; Guizhen Kan; Shiyou Cui; Qingchang Meng; Junyi Gai; Deyue Yu (Euphytica, 2009)

Analysis of Cry1Ab toxin bioaccumulation in a food chain of Bt rice, an herbivore and a predator - Mao Chen; Gong-yin Ye; Zhi-cheng Liu; Qi Fang; Cui Hu; Yu-fa Peng; Anthony M. Shelton (Ecotoxicology, 2009)